Projected increase in global runoff dominated by land surface changes - Zhou, Sha; Yu, Bofu; Lintner, Benjamin R.; Findell, Kirsten L.; Zhang, Yao (Nature climate change, 2023)
Increases in atmospheric CO 2 concentration affect continental runoff through radiative and physiological forcing. However, how climate and land surface changes, and their interactions in particular, regulate changes in global runoff remains largely unresolved. Here we develop an attribution framework that integrates top-down empirical and bottom-up modelling approaches to show that land surface changes account for 73–81% of projected global runoff increases. This arises from synergistic effects of physiological responses of vegetation to rising CO 2 concentration and responses of land surface—for example, vegetation cover and soil moisture—to radiatively driven climate change. Although climate change strongly affects regional runoff changes, it plays a minor role (19–27%) in the global runoff increase, due to cancellation of positive and negative contributions from different regions. Our findings highlight the importance of accurate model representation of land surface processes for reliable projections of global runoff to support sustainable management of water resources. Global runoff is subject to multiple influences with high uncertainties in its projections. The authors show that global runoff is expected to increase mainly due to vegetation and soil moisture responses to rising CO 2 and radiative forcing, rather than through direct effects of climate change.